IDENTIFIKASI KAWASAN ABRASI DAN AKRESI SEPANJANG GARIS PANTAI KECAMATAN KOTO TANGAH KOTA PADANG - Yulia Reza Putri; Dwi Marsiska Driptufany, Ilham Armi, Dwi Arini, Defwaldi (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2023)
The coastline is an important component in determining the boundaries of a country's territory and regional autonomy. Changes in coastlines can take the form of land reduction (abrasion) or land increase (accretion). The aim of this research is to identify changes in the coastline of Koto Tangah District, Padang City from 2003 to 2023 and identify areas of abrasion and accretion on the coast of Koto Tangah District from 2003 to 2023. This research uses the DSAS (Digital Shoreline Analysis) method. System) carried out on ArcGis 10.8 software. The results obtained in this research are that the coastline of Koto Tangah District has changed every year from 2003, 2008, 2013, 2018, and 2023 based on observations and sampling using Geodetic GPS at 332 points. The samples were in Koto Tangah sub-district, then the results of the analysis carried out by the researchers showed that there were significant changes in the coastline in the observation period from 2003-2023, which experienced more accretion, amounting to 232 points, compared to abrasion, amounting to 100 points.